Synthesis and Dielectric Properties of Magnesium Silicate Hydrate Deposited With SnO2 - Yüksel Akınay (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, the dielectric properties of SnO2 coated Magnesium Silicate Hydrate (MSH) pigments were evaluated. The SnO2 coated MSH pigments were obtained by chemical reduction method with the 3:7 SnO2/MSH ratio by weight. The structural and dielectric properties of this pigment and MSH were investigated. The surface morphology and phase types were determined by scanning electron microscope (SEM) and x-ray diffraction (XRD). The bond types were characterized by Fourier Transform Infrared Spectrophotometer (FT-IR). The surface of MSH was uniformly coated with SnO2 as accepted in the SEM images. The existence of XRD peaks for SnO2 nanoparticles proves the presence of SnO2 coating. The dielectric properties of prepared pigments were measured via vector network analyzer (VNA) in the frequency range of 8.2–12.4 GHz (X-Band). The dielectric properties of SnO2 deposited MSH pigments were obtained to be about almost 3-4 times than MSH in the 8-12 GHz frequency range. This study is the first report for the dielectric properties of SnO2 deposited MSH pigments.